Investment Opportunities in Emerging Markets: A Case Study of India - Jain, Ridhima (2006)
An emerging market is defined as a capital market in a developing country. If a country's GNP per capita did not achieve the World Bank's threshold for a high-income country, then that country's market was considered an emerging market. In the investment world, the continuing demand for higher return and lower risk have fuelled a recent surge of interest in investing in "emerging markets". India is one of the biggest and fastest-growing developing economies and has attracted the most investor attention in recent years. After liberalization of the Indian economy in 1991, it has become one of the hotspots for global investment. Foreign investment (both foreign direct investment and foreign institutional investment) further enhanced India's economic growth and helped in transforming several sectors of the Indian Industry into globally competitive entities. India is also the world's second fastest gowing economy and boasts of highly competitive private companies, a booming stock market, and a modern, well-disciplined financial sector. The Indian stock markets witnessed unprecedented buoyancy during 2005-06. Strong macro-economic fundamentals, positive investment climate and sound business outlook drove the bullish trend. This research studies the growth of six key Indian Industries (Steel, Cement, Auto, Banking, Power and Telecommunication) over the past five years. The results show that the industries have recorded a robust growth during this time period and create great opportunities for investment. Further, the research compares India with four other leading developing countries (Brazil, Russia, China and South Africa) during 2005-06 and concludes that India is one of the fastest rising stars among all these major emerging economies with its economic growth rate running at over 8% annually.